A highly green approach towards aromatic nitro group substitutions: catalyst free reactions of nitroimidazoles with carbon nucleophiles in water. Issue 36 (8th June 2020) - Shah, Syed Raza; Ali, Muhammad; Anwar, Muhammad U.; Al-Harrasi, Ahmed
Abstract : We have successfully developed a flexible green aqueous approach for the formation of a carbon–carbon bond by the reaction of highly-enolizable carbanions (mostly derived from 1, 3-dicarbonyl compounds) with an aromatic carbon bearing a nitro group. Abstract : We have successfully developed a flexible green aqueous approach for the formation of a carbon–carbon bond by the reaction of highly-enolizable carbanions (mostly derived from 1, 3-dicarbonyl compounds) with an aromatic carbon bearing a nitro group. The key step involves a nucleophilic displacement reaction. All newly synthesized compounds were unambiguously characterized via various spectroscopic techniques including NMR, mass spectrometry and single-crystal X-ray diffraction as applicable. We believe that our study will be useful in providing new insights into catalyst-free water-mediated nucleophilic substitution reactions.